2020
DOI: 10.2196/13046
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Privacy Risks of Patients’ Data in China: Case Study

Abstract: Background Patient privacy is a ubiquitous problem around the world. Many existing studies have demonstrated the potential privacy risks associated with sharing of biomedical data. Owing to the increasing need for data sharing and analysis, health care data privacy is drawing more attention. However, to better protect biomedical data privacy, it is essential to assess the privacy risk in the first place. Objective In China, there is no clear regulation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The workflow for this study is shown in Figure 1 . In the privacy risk experiment of the PHIs, 16 limited data sets were generated, with each comprising one of the 16 PHIs merged with five common demographic variables (Year_of_birth, Gender_concept_id, Race_concept_id, Ethnicity_concept_id, and State), as in previous clinical studies [ 53 , 54 ]. For example, Condition_start_date, which is the name of data set 1 of the 16 limited data sets, consists of one PHI (Condition_start_date variable) and five common demographic variables.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The workflow for this study is shown in Figure 1 . In the privacy risk experiment of the PHIs, 16 limited data sets were generated, with each comprising one of the 16 PHIs merged with five common demographic variables (Year_of_birth, Gender_concept_id, Race_concept_id, Ethnicity_concept_id, and State), as in previous clinical studies [ 53 , 54 ]. For example, Condition_start_date, which is the name of data set 1 of the 16 limited data sets, consists of one PHI (Condition_start_date variable) and five common demographic variables.…”
Section: Methodsmentioning
confidence: 99%
“…Through the PHI and QI privacy risk experiments, we measured privacy risk in terms of the following two aspects: (1) measurements based on the number of total records in each data set and (2) measurements based on the identical number of records through random sampling from each data set. In the first aspect, we considered that clinical studies perform analysis with clinical tables according to clinical scenarios [ 16 , 59 - 61 ]; thus, we measured privacy risk with the number of total records in the data set generated by referring to previous studies [ 53 , 54 ]. With the number of total records, we compared the limited and safe harbor data sets based on the total records of each PHI and QI.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the users on the syndromic surveillance system consented sharing the necessary information for using this system. Data security and privacy protection were particularly emphasized with administrative as well as technical support [17] throughout the deployment of the system. Standard security settings and software (eg, firewalls, data encryption) were implemented.…”
Section: Ethics Review Privacy Protection and Data Securitymentioning
confidence: 99%